Does dexmedetomidine as a neuraxial adjuvant facilitate better anesthesia and analgesia? A systematic review and meta-analysis. - Huang-Hui Wu; Hong-Tao Wang; Jun-Jie Jin; Guang-Bin Cui; Ke-Cheng Zhou; Yu Chen; Guo-Zhong Chen; Yu-Lin Dong; Wen Wang (PLoS ONE, 2014)
Background Neuraxial application of dexmedetomidine (DEX) as adjuvant analgesic has been invetigated in some randomized controlled trials (RCTs) but not been approved because of the inconsistency of efficacy and safety in these RCTs. We performed this meta-analysis to access the efficacy and safety of neuraxial DEX as local anaesthetic (LA) adjuvant. Methods We searched PubMed, PsycINFO, Scopus, EMBASE, and CENTRAL databases from inception to June 2013 for RCTs that investigated the analgesia efficacy and safety for neuraxial application DEX as LA adjuvant. Effects were summarized using standardized mean differences (SMDs), weighed mean differences (WMDs) or odds ratio (OR) with suitable effect model. The primary outcomes were postoperative pain intensity and analgesic duration, bradycardia and hypotension. Results Sixteen RCTs involving 1092 participants were included. Neuraxial DEX significantly decreased postoperative pain intensity (SMD, -1.29; 95% confidence interval (CI), -1.70 to -0.89; P<0.00001), prolonged analgesic duration (WMD, 6.93 hours; 95% CI, 5.23 to 8.62; P<0.00001) and increased the risk of bradycardia (OR, 2.68; 95% CI, 1.18 to 6.10; P = 0.02). No evidence showed that neuraxial DEX increased the risk of other adverse events, such as hypotension (OR, 1.54; 95% CI, 0.83 to 2.85; P = 0.17). Additionally, neuraxial DEX was associated with beneficial alterations in postoperative sedation scores and number of analgesic requirements, sensory and motor block characteristics, and intro-operative hemodynamics. Conclusion Neuraxial DEX is a favorable LA adjuvant with better and longer analgesia. The greatest concern is bradycardia. Further large sample trials with strict design and focusing on long-term outcomes are needed.